Effects of neighbourhood social cohesion and need for restoration on restorative experiences. Issue 4 (12th August 2020) - Feng, Ningning; Zhang, Airong; Cui, Lijuan; Zeng, Huaming; Mankad, Aditi
Abstract : Restorative experience refers to an experience of psychophysical restoration from stress and mental fatigue during people‒environment interactions. Previous research has documented the influence of neighbourhood physical environment on restorative experiences; however, it is still unclear whether neighbourhood social environment can affect restorative experiences. Applying a socioecological perspective, the current study aims to explore the effect of neighbourhood social cohesion on restorative experience and to examine whether people's need for restoration would moderate this effect. After manipulating the need for restoration in terms of antecedent attentional state, participants ( N  = 244) with and without the need for restoration read one of three experimental scenarios describing a neighbourhood with high, neutral, or low social cohesion. Participants reported their restorative experience pre‐ and post‐exposure to neighbourhood social cohesion scenarios. Results showed that participants in the high social cohesion neighbourhood condition perceived more post‐exposure restorative experience than did those in the neutral or low cohesion conditions. Restorative experience increased from pre‐ to post‐exposure in the high social cohesion condition; the increase was greater for participants with the need for restoration. On the other hand, restorative experience decreased from pre‐ to post‐exposure in the low social cohesion condition for participants without the need for restoration. These findings suggested that a socially cohesive neighbourhood could enhance individuals' restorative experiences and that the strength of this restorative benefit might depend on the need for restoration.